18F-FDG PET/CT in Osteoradionecrosis of the Hyoid. (January 2021) - Antippa, Sophia Huntley; Du, Leanne; Price, Nathan; Hsu, Charlie Chia-Tsong
Abstract : Abstract: Osteoradionecrosis (ORN) is a well-documented complication following radiation treatment for head and neck malignancy. Facial bones, mainly the mandible, laryngeal cartilage, and skull, are frequently involved sites for ORN. A rare site for ORN is the hyoid, with very limited cases described in the literature. Recognition of the imaging pattern of hyoid ORN is critical to avoid misdiagnosis of recurrent disease, prompting early treatment.